Pengaruh Keselamatan dan Kesehatan Kerja (K3) serta Standar Operasional Prosedur (SOP) Terhadap Kinerja Karyawan di PT. PLN (Persero) ULP Paniki - Agnes Tasya Palit; Christien Adriani Karambut; Wingston Markus Jusuf Longdong (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2024)
This research aim is to analyze the influence of occupational health and safety variables and standard operating procedures (SOP) on employee performance at PT. PLN (Persero) ULP Paniki. Occupational health and safety and SOP implementation are considered to have significant roles in creating a comfortable and effective work environment that supports optimal employee performance. The research employs a quantitative approach and a survey method involving 50 respondents from workers at PT. PLN (Persero) ULP Paniki. The research results show that there is a positive and significant relationship between occupational health and safety variables and employee performance. This finding indicates that the implementation of effective occupational health and safety programs contributes to the increase in employee performance. Furthermore, the analysis results also state that standard operating procedures (SOP) have a strong positive influence on employee performance. Based on these research findings, the recommendations proposed emphasize the need for increased investment in occupational health and safety programs, as well as a more efficient approach in delivering and explaining SOP within the PT. PLN (Persero) ULP Paniki area. Thus, the industry can create a more comfortable and effective work environment that fosters the achievement of optimal employee performance.